Socioeconomic Disadvantage, Mental Health and Substance Use in Young Men in Emerging Adulthood. Issue 1 (2nd January 2021) - Currier, D.; Patton, G.; Sanci, L.; Sahabandu, S.; Spittal, M.; English, D.; Milner, A.; Pirkis, J.
Abstract: Emerging adulthood is a neglected phase of the life course in health research. Health problems and risk behaviors at this time of life can have long-term consequences for health. The 2016 Lancet Commission on Adolescent Health and Wellbeing reported that the influence of socioeconomic factors was under-researched among adolescents and young adults. Moreover, the influence of socioeconomic factors on health has been little researched specifically in emerging adult men. We aimed to investigate associations between socioeconomic disadvantage and mental health, suicidal behavior, and substance use in young adult Australian men. Logistic regression was used to examine the association between Year 12 (high school) completion and area disadvantage on mental health, suicidal behavior, and substance use in 2, 281 young men age 18–25 participating in the Australian Longitudinal Study on Male Health (Ten to Men). In unadjusted analysis both Year 12 non-completion and area disadvantage were associated with multiple adverse outcomes. In adjusted analysis Year 12 non-completion, but not area disadvantage, was associated with poorer mental health, increased odds of suicidal behavior, and substance use. Retaining young men in high school and developing health-promotion strategies targeted at those who do exit education early could both improve young men's mental health and reduce suicidal behavior and substance use in emerging adulthood.